ANALISIS CAR, NPF, BOPO DAN FDR TERHADAP PROFITABILITAS PADA BANK SYARIAH DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Ahmad Afwan Alwi; Novianda Zulti; ElyantiRosmanidar ElyantiRosmanidar; Usdeldy Usdeldy (Bajang Institute, 2023)
This study has the objective of conducting a Systematic Literature Review (SLR) on Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), Operating Costs and Operating Income (BOPO), and Financing Deposit To Ratio (FDR) on Profitability at Bank Syariah Indonesia in 2017- 2022[A1]. This review uses data collection methods from journals related to CAR, NPF, BOPO and to the Profitability of Bank Syariah Indonesia. The results of the research question (RQ: 1) on the method that is often used to conduct research related to the influence of CAR, NPF, BOPO and FDR on Profitability in Islamic Banks in Indonesia, the results obtained are the paper category based on the data collection technique using secondary data collection techniques in the form of Annual Report on Islamic banks through the official website as well as data in OJK (Financial Services Authority) publications. Furthermore, the results of the research question (RQ: 2), namely the journal that has the most significant effect of financial ratios on the profitability of Islamic Banks, there are 12 journals that analyze that every year there are journals that discuss this matter, even the most in 2022 are several journals with a quantitative approach. The results for the research question (RQ: 3) are about the factors that influence financial ratios on profitability, the results obtained are paper categories based on factors that affect profitability. That the greater the CAR value, the higher the NPF level, the lower the costs incurred and the amount of income or BOPO and the suitability of raising funds and distributing financing or FDR has an effect on the Profitability of Islamic Banks in Indonesia based on research in these papers.